Pathogenicity evaluation of GVI-1 lineage infectious bronchitis virus and its long-term effects on reproductive system development in SPF hens - Bo, Zongyi; Chen, Shuqin; Zhang, Chengcheng; Guo, Menjiao; Cao, Yongzhong; Zhang, Xiaorong; Wu, Yantao (Frontiers in Microbiology, 2022)
Infectious bronchitis virus (IBV) has gained increasing attention in the poultry industry due to its ability to cause clinical signs not only in the respiratory system and kidney but also in the reproductive system of layers. Recently, the GⅥ-1 genotype IBVs have spread widely in China, whereas their pathogenicity in egg-laying chickens has rarely been studied, especially its long-term influence in egg production upon the early infection in chicks. In this study, 10-day-old SPF chicks were infected with the GⅥ-1 genotype JX181 strain and monitored over a 170-day period after infection. The pathogenicity evaluation of the JX181 strain included clinical observations, immunohistochemical assay, viral load, viral shedding, gross autopsy, and laying rate. The results showed that JX181 has a high pathogenic, causing severe system lesions, and the decrease in egg production. In summary, this study describes the long-term impact of early infection with the IBV GⅥ-1 genotype on the reproductive system of hens, providing a comprehensive understanding of the pathogenicity of the IBV GⅥ-1 genotype and emphasizing the importance of its early prevention.